The art of staying neutral : the Netherlands in the First World War, 1914-1918 - Abbenhuis, Maartje (Amsterdam University Press, 2006)
Offers a comprehensive and insightful account of the history of the Netherlands and its neutrality in the First World War, taking into account domestic and international implications.